Nutritional Status Related to Work Fatigue in Police Officers at the Traffic Police Directorate of East Java - Antika, Karinda Kennia; Pramono, Adriyan (Universitas Negeri Semarang, 2022)
Work fatigue can cause a decrease in performance which can lead to work accidents. Fatigue can be caused by several factors including nutritional status and work environment. This study aimed to determine the relationship between nutritional status and work environment with work fatigue of Police Officer at The Traffic Police Directorate of East Java. The design of this study was cross sectional, with 44 subjects aged 21-40 years. Data collection includes body weight and body height, subject identity data and work fatigue levels with the Industrial Fatigue Research Committee (IFRC) questionnaire. The independent variables were nutritional status and work environment and the dependent variables was work fatigue. Spearman’s Rank and Kolmogorov Smirnov test was used to analyze the relationship between nutritional status and work environment variables with work fatigue on the subjects. The correlation analysis between nutritional status and work fatigue was p = 0,000. The analysis between work environment and work fatigue was p = 1,000. There was a relationship between nutritional status and work fatigue, but there was no relationship between work environment and work fatigue of Police Officer at The Traffic Police Directorate of East Java.